The Inconstant Gardener: Exile, Madness, and the Postcolonial Subject in Bessie Head s A Question of Power - Tynan, Avril (Ecocene: Cappadocia journal of environmental humanities, 2023)
Gardens are a complex meeting place of nature and culture, shaped simultaneously by the natural resources and environmental limitations of the land and by the social, political, economic, and historical values and possibilities exploited by those who fashion and tend them. In Bessie Head’s A Question of Power(1974), the protagonist seeks out, in her garden, a restorative ground for resolution and progress; yet the same space stages uncomfortable encounters animated by hierarchies of power and acts of misappropriation. Through discussion of community gardens and cultural notions of uprootedness, I argue that the community garden is a site of economic security, cultural independence, and social belonging. The protagonist, an exile suffering from psychotic hallucinations, gains from the garden a means of grounding and rooting herself in a new land, countering narratives of uprootedness, estrangement, and illness. Yet, moving away from the purely redemptive and reparative readings of the garden, I argue that thegarden remains an ambivalent space nourished by the co-existence of incongruous histories and identities, where progress is unsteady, inharmonious, and uncanny. To plant a garden is ultimately not to produce a world beholden to the gardener’s will but to cultivate a space in which the gardener comes to realize their own entangled position among others. ..